THE VIEWS OF 6TH GRADERS ABOUT CHANGE AND CONTINUITY OF WEDDINGS and FEASTS - Nil DUBAN; Ramazan YILDIRIM (International Journal of Eurasia Social Sciences, 2017)
Both wedding ceremonies and festivals are among the most significant parts of culture and these rituals contain many cultural elements. This study aims at uncovering how students perceive and make sense of the change and continuity in the framework of wedding ceremonies and festivals. The study was designed as a phenomenological research, which is part of qualitative research. The data of the study were collected through semi-structured interviews conducted both as a pre- and a post-test. The participants of the study were six students who were attending Şehitler secondary school in the central district of Kutahya. They were chosen using the criterion sampling technique, which is one of the purposeful sampling methods. Interviews with the participants were carried out in face-to-face manner. Following the initial meetings with the students the implementation was carried out in the courses. The implementation included the lecture on wedding ceremonies and festivals to reveal their existing information about the topics. In addition, teachers also provided background information about wedding ceremonies and festivals and a discussion followed it. Then, the materials from the written sources were given to the students, which were about the past wedding ceremonies and festival rituals. In addition, they listened to recordings from local people to inform them about the local wedding ceremonies and festivals. Finally, the students were asked to make a comparison of the past and current wedding ceremonies and festivals in terms of the changes and continuity of cultural elements. Their observations and comparisons concerning the topic were discussed in the course. Both pre- and post-implementation interviews were recorded. Following the transcription of the interview data the content analysis was employed. The findings were analyzed under four headings: wedding ceremonies, circumcision feast, festivals and cultural transfer from the perspective of the participants. Each heading is given as follows together with sub-themes and categories. The sixth grade students participated in the study is found to have significant information about the current wedding ceremonies and festival rituals. Their knowledge about the past practices seems to be gained through family members or through courses. Some participants reported that some of the past practices should continue, while the others reported that they should not. In order to maintain the continuity of traditions parents should be model for their children.